Freedom and integrity. Relationships and assault - VanBrunschot, Erin Elan Gibbs (The British journal of criminology, 2003)
Physical assault transgresses the symbolic and physical boundaries associated with the body. Perceptions of the boundaries surrounding one's own and other bodies vary, however, depending upon the relationship between interacting parties. Through an examination of a random sample of assault incidents, this study highlights the victim-offender relationship by considering the contexts of assault. Using assault narratives generated from police witness statements, assaults are examined to determine how actions and interpretations appear influenced by the relational proximity of the interacting other. Issues of personal freedom and personal integrity appear as more or less significant depending upon the perceived symbolic and physical boundaries that specific relationships imply